Ragam Bahasa Ngalam dalam Media Sosial Instagram: Kajian Sosiolinguistik - Icha Precilla Hariyanto Putri (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
Indonesia as a country that has a geographical location makes it a country with a variety of cultures, one of which is language. Language as a means of communication makes it one of the most important things for humans, considering that humans also cannot be separated from other people. The number of languages in Indonesia, this results in a variety of languages. Language variety arises because of social interaction in the community in an area. This is based on a sociolinguistic study that emphasizes the science that studies the language that exists in society. Each region must have a language problem object. This is why the writer has the intent and purpose to find out social events in language that occur in society, especially the city of Malang. The variety of ngalam languages that characterize the city of Malang is often referred to as walikan language, which means the opposite. Apart from the Walikan language, the various Ngalam languages still have their own characteristics that distinguish them from other Walikan languages. This study uses a qualitative descriptive type method that is descriptive and analytical. Instagram with three accounts is the object of this research. From the results of research conducted on Instagram, it is known that the diversity of the ngalam language is found in the three accounts of the object of study. The author finds that there are many forms of conveying various languages even though it is only through one social media.Keywords: Variety of Ngalam, Malang, social media, Instagram